2014
DOI: 10.1093/ndt/gfu044
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic abnormalities in autosomal dominant polycystic kidney disease

Abstract: Autosomal dominant polycystic kidney disease (ADPKD) is the most common inherited kidney disorder and is known to affect all ethnic groups with a prevalence of 1:400-1:1000 live births. The kidney in ADKPD is characterized by the formation of numerous cysts which progressively expand and eventually destroy normal kidney structure and function. Cysts occur in other organs outside the kidney, most commonly in the liver, pancreas and spleen. Important non-cystic features include intracranial aneurysms and cardiac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 67 publications
1
23
0
1
Order By: Relevance
“…Currently, the link between polycystin function and insulin resistance, in ADPKD patients with preserved renal function, is still poorly known [41], even if recently Mao et al . [42] showed that polycystin proteins could regulate insulin secretion, being expressed in pancreatic islet beta cells. Other significant metabolic alterations were observed in ADPKD patients in our study, like higher Hcy and SUA respect to control group.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the link between polycystin function and insulin resistance, in ADPKD patients with preserved renal function, is still poorly known [41], even if recently Mao et al . [42] showed that polycystin proteins could regulate insulin secretion, being expressed in pancreatic islet beta cells. Other significant metabolic alterations were observed in ADPKD patients in our study, like higher Hcy and SUA respect to control group.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, it was of extreme interest to the field of ADPKD when a similar high rate of aerobic glycolysis and glucose dependence was identified in ADPKD kidney tissue and relevant mouse models [56, 103, 104]. Mechanistic analyses indicated that the defect represented inhibition of LKB1/AMPK signalling, coupled with strongly elevated levels of mTORC1.…”
Section: Adpkd and The Hallmarks Of Cancermentioning
confidence: 99%
“…The later cyst expansion is caused by enhanced epithelial cell proliferation, fluid secretion, detachment from the original tubular structure, abnormal extracellular matrix, altered gene expression and cell polarity, inflammation, increased apoptosis and environmental factors [4,6,7]. Cyst formation also occurs in the liver, pancreas and spleen; intracranial aneurysms and cardiac valve defects may be present as well [8].…”
Section: Introductionmentioning
confidence: 99%